Analisis Faktor-Faktor Yang Memengaruhi Pengguna Snapchat Membagikan Video Dengan Menggunakan Structural Equation Modeling - Khusnatul Mukaromah; Ari Kusyanti; Andi Reza Perdanakusuma (Fakultas Ilmu Komputer (FILKOM), Universitas Brawijaya, 2018)
Snapchat is one of the social media that have main feature when user can share videos and photos a few seconds on home they are then automatically deleted after 24 hours. Bloomberg reports that collected Kompas Tekno in June 2016 each day as many as 150 million users using filter photos or video at snapchat, and experienced a rise from the previous years 110 million to 140 million active users daily. Every day, users share video live their activities on othe users snapchat as well as providing some personal information while signing up for an account on snapchat such as name, email, and phone number. Currently many users who give too much information on sosial media because they do not care about the privacy and security on the sosial media used. Therefor, the objective of this research is to analyze the factors that effect the users share their live video on snapchat using 10 latent variable and 1 variable secondary order. The data were analyze, collected from respondents is 282 active users snapchat. Data from respondent were analyze using method analyze Structural Equation Modelling (SEM).